Software tool for processing and selecting objects in infrared images - V. A. Rybak; Rabia Amro (Системный анализ и прикладная информатика, 2023)
The article describes the scientific problem of processing images obtained in the infrared range. Methods for filtering such images in order to reduce noise are presented. Methods for optimal smoothing are described. A software tool has been developed that allows you to select the desired objects on the processed images.